Cereal Grains - Volume 1 2021
DOI: 10.5772/intechopen.98745
|View full text |Cite
|
Sign up to set email alerts
|

Salinity Stress in Maize: Effects of Stress and Recent Developments of Tolerance for Improvement

Abstract: Soil salinity has emerged as a global threat to sustainability of farming systems by deteriorating the quality and productivity of crops particularly in the coastal regions of the world. Although, as a C4 plant, maize (Zea mays L.) has ability to tolerate a medium level of salinity; but initial growth stages of maize are sensitive to salinity stress. Therefore, it is crucial to expand our understanding pertaining to maize response to salt stress and tolerance mechanisms for devising approaches to enhance maize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 113 publications
0
8
0
Order By: Relevance
“…It has been reported that soil salinity is one of the significant threats to maize production worldwide [31]. In general, maize shows decreased germination rate, stunted growth, reduced photosynthesis and less productivity under salinity stress [32,33]. However, maize production needs to be doubled, even under salinity stress, by 2050 to meet the ever-increasing demand of maize as a fundamental foodstuff [34].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that soil salinity is one of the significant threats to maize production worldwide [31]. In general, maize shows decreased germination rate, stunted growth, reduced photosynthesis and less productivity under salinity stress [32,33]. However, maize production needs to be doubled, even under salinity stress, by 2050 to meet the ever-increasing demand of maize as a fundamental foodstuff [34].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the use of Bch affects the absorption of nutrients and water and causes an increase in RWC and a decrease in ion leakage under salinity stress conditions . Also, the combination of Bch and AMF improves growth and water absorption by inducing the expression of speci c genes and balancing plant hormones [52][53][54][55][56][57][58][59][60].…”
Section: Ion Leakage and Rwcmentioning
confidence: 99%
“…Salinity decreases the growth and grain yield of Z. mays while there is no application of mitigating strategies. The most critical phases for plant development are germination and seedling growth, and maize is more sensitive to salinity at these stages [5,6].…”
Section: Introductionmentioning
confidence: 99%